TEACHING WRITING USING DISCOVERY LEARNING - Cintia Khoerun Nisa; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2024)
The objective of this research is to investigate the students’ difficulties in writing using discovery learning. Descriptive qualitative research design was employed in this research. The subject of this research was the eighth-grade students of MTs. Az-Zahra Batujajar in the academic year 2020/2021. The data of this research was obtained from the questionnaire and test. The instrument consists of 5 statements that indicate aspects of writing there were organization, content, grammar, mechanism, and vocabulary. The result of this research is that most of the students have difficulty in grammar. Based on data the questionnaire 90% of students stated difficulties in the grammar aspect, and supported by data from the test that the lowest average score of students in the grammar aspect is 71. It can be concluded that the highest difficulty of students when writing recount text is grammar.